2005
DOI: 10.5194/acp-5-1679-2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pathways of tropospheric nitrophenol formation from benzene and phenol using a multiphase model

Abstract: Abstract. Phenols are a major class of volatile organic compounds (VOC) whose reaction within, and partitioning between, the gas and liquid phases affects their lifetime within the atmosphere, the local oxidising capacity, and the extent of production of nitrophenols, which are toxic chemicals. In this work, a zero-dimension box model was constructed to quantify the relative importance of different nitration pathways, and partitioning into the liquid phase, of mono-aromatic compounds in order to help elucidate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…It mainly included biomass burning in nearby farmlands and rural areas and smoke from restaurants and residential kitchens. The direct emission of nitrated phenols from biomass burning was confirmed and determined by several previous studies, with emission factors ranging from 0.4 to 11.1 mg kg −1 (Hoffmann et al, 2007;Iinuma et al, 2007;Wang et al, 2017b).…”
Section: Temporal and Spatial Variationsmentioning
confidence: 59%
See 2 more Smart Citations
“…It mainly included biomass burning in nearby farmlands and rural areas and smoke from restaurants and residential kitchens. The direct emission of nitrated phenols from biomass burning was confirmed and determined by several previous studies, with emission factors ranging from 0.4 to 11.1 mg kg −1 (Hoffmann et al, 2007;Iinuma et al, 2007;Wang et al, 2017b).…”
Section: Temporal and Spatial Variationsmentioning
confidence: 59%
“…However, the formation pathways of nitrated phenols from the condensed phase remains more uncertain than those for the gas phase (Harrison et al, 2005a). Once formed in the gas phase, the phenols and nitrated phenols partition between the gas and particle phases according to their saturated vapor pressure (Nojima et al, 1975;Bolzacchini et al, 2001;Harrison et al, 2005b;Xu and Wang, 2013). Chow et al (2016) found evidence from field measurements that high levels of nitrated phenols in Hong Kong were associated with high concentrations of NO 2 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Aqueous phase formation of 4-nitrophenol has also been proposed by Harrison et al (2005), suggesting that once phenol is produced from the reaction of benzene and the OH radical, it partitions into the aqueous phase and reacts with NO 3 to form 4-nitrophenol, which then partitions favorably into the gas phase. Based on model calculations, the aqueous formation processes can have a substantial contribution to the total formation rate at high liquid water content, such as in clouds, but this process contributes less than 2 % to nitrophenol formation at low liquid water contents (Harrison et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Precursors such as phenols and cresols are emitted and produced via photochemical oxidation of benzenes, and nitration processes then occur with the participation of NO 2 . During this process, the phenols and nitrated phenols partition from time to time between the gas and particle phases according to their saturated vapor pressure (Nojima et al, 15 1975;Bolzacchini et al, 2001;Harrison et al, 2005b;Xu and Wang, 2013). Chow et al (2016) found evidence from field measurements that high levels of nitrated phenols in Hong Kong were associated with high concentrations of NO 2 .…”
Section: Introductionmentioning
confidence: 99%